2016
DOI: 10.5897/ajar2016.11670
|View full text |Cite
|
Sign up to set email alerts
|

Phenology, yield and fruit quality of four persimmon (Diospyros kaki L.) cultivars in So Paulos Midwest countryside, Brazil

Abstract: The aim of this study is to evaluate the phenology, yield and fruit physicochemical characteristics of four persimmon cultivars (Diospyros kaki L.) in São Paulo's Midwest countryside, Brazil. The persimmon cultivars studied were 'Pomelo', 'Rama Forte', 'Fuyu' and 'Rubi'. The main phenological phases of persimmons trees were evaluated. Despite significant differences between cultivars in the early and intermediate stages of the plants development such as branch development, full blossom and fruiting's onset, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Previous research reported the differences in flowering periods, characteristics of flower and fruit occurring in several cultivars planted in the same environment, such as in the persimmon (da Silva et al 2016), three citrus species (Sharma et al 2017), peach (Alves et al 2018). Pummelo in Magetan region generally bloomed from October to November.…”
Section: Introductionmentioning
confidence: 97%
“…Previous research reported the differences in flowering periods, characteristics of flower and fruit occurring in several cultivars planted in the same environment, such as in the persimmon (da Silva et al 2016), three citrus species (Sharma et al 2017), peach (Alves et al 2018). Pummelo in Magetan region generally bloomed from October to November.…”
Section: Introductionmentioning
confidence: 97%